Professional Mosque Management Model Based on Religious and Academic Activities in the Community - Fernando, Riky; Hasanuddin, Tubagus; Rangga, Kordiyana K.; Utama, Dimas Duta Putra (Khalifa Journal of Islamic Education, 2022)
This study aims to analyze how the Al Bariyah Mosque is managed as a professional mosque model in the community of Hajimena Natar village, South Lampung, Lampung Province, Indonesia. The research was carried out using a qualitative method with a case study approach (single-case study). Sources of data were taken to several informants through in-depth interviews. The writer also took data by observation and document analysis to strengthen the interview data. All data were then analyzed using the Miles and Huberman technique with the stages of collecting, reducing and analyzing data and drawing conclusions. Overall, the research findings found three forms of the Al Bariyah Mosque management process so that it becomes a professional mosque; the three approaches are i) direct supervision starting from planning to an evaluation of activities by mosque administrators, ii) involving the community activities in every planned mosque activity. , iii) establishing a transparent, professional and accountable mosque management. The findings in the study can be used as an example for other mosque administrators to manage mosques professionally in the community.